Impact of Sodium and Magnesium on Low-Temperature Oxidation of Coal - Tang1, Yibo; Li2, Zenghua; Ma2, Dongjuan (Asian Journal of Chemistry, 2014)
Apart from the elements like C, H, O and N, other mineral elements are also found in the composition of coal, which influence the low-temperature oxidation of coal. Five kinds of inorganic additive (Na and Mg) were added into the coal samples for the programmed-heating experiments. Then the O2 consumption, CO2 and CO generation were tested. Interfering by the magnesium or sodium reagent, the concentration on O2 consuming, CO2 and CO producing for the treated coal all decreased evidently. Furthermore, some inorganic minerals can react with coal molecules and form stable structure, which resulting in the suppression in the oxidation of coal.